Poetikkens kunstformer: Om forholdet mellem poesi og poetik i Niels Lyngsøs MORFEUS - Schweppenhäuser, Jakob (K&K - Kultur og Klasse, 2009)
Art Forms in Poetics: On the Relationship between Poetry and Poetics in Niels Lyngsø’s MORFEUS: In Denmark, the genre of poetics has to a high degree developed into poets’ own reflections on their literary work and working process. This turn has resulted in a textual hybridity, restlessly oscillating between essayistic-theoretical orientation and poetic discourse. It has been pointed out that scholars have generally failed to pay attention to the artistic elements of such poetological writings. This is where this article takes its point of departure, probing Danish poet Niels Lyngsø’s abundant, complex and ambitious bastard piece MORFEUS from 2004 – a blend of visual poetry, sonnets, associative lists, essays on literature and the arts and many other forms. Inserted in a slipcase, the large quadratic, unpaged sheets, fastened with metal rings, seem extremely tactile; the reader becomes a percipient, a sensing body. As the poetry and the poetics are inseparably wrapped in each other, the poetic, sensuous perception mode is encouraged to be transferred to the ordinarily content-orientated reading of theoretical reflections. The point is now that this transfer turns out to be fruitful: the poetic function is at times strikingly operative. Passages where this is the case are analysed profoundly and the implications and perspectives of this fusion of poetry and poetics are unfolded.